(3GdeUGOQs - (3GdMSjfj Hf CMeO Hf GdMSjfj GdRhRfj, CHh YHO Gddg,J (B486 (3g` s
(3ChdgG (B:s
(3GdMeO dgd Ydi ShGHZ GdGAg GdeJSGHbI GNhGLG aEf gPg eUGOQ JQLeJgG hfaMJgG hLQOJgG Yf ThGgO GdMOjK hGdGTYGQ hGdGeKGd s
(3BNQgG (B:s
(3hGdbGHQ cPdc fbVj Led GdKdGKj s
(3GdJYbjHI hgh YHGQI Yf JQLeI HGdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B231s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs